Photo gallery: Ground zero Nagasaki. (24th May 2016) - Nakamura, Akitoshi
Abstract: This selection of photos is meant as an appeal from the Nagasaki Atomic Bomb Museum to remember the atomic bombing of Nagasaki on 9 August 1945. It was compiled by museum director Akitoshi Nakamura based on the collection at the Nagasaki Atomic Bomb Museum. 1 Readers are invited to visit the Nagasaki Atomic Bomb Museum and spend some time viewing its collection of over 1, 000 photographs and remnants from the city at that time to get a sense of what happened before and after the atomic bombing that summer seventy years ago, and how devastating the atomic bomb's destructive effects were.